Mechanical properties of honeycomb structure with zero Poisson’s ratio for flexible trailing edge - ZHOU Yue; LI Bo; XU Weiwei; WEN Youyi (Journal of Aeronautical Materials)
To provide technical support for the design of new seamless flexible trailing edge structures，a comparative study of the elastic properties of four novel zero Poisson’s ratio honeycomb structures（sinusoidal-type，V-type，segmented sinusoidal-type and cosine-type）is conducted through theoretical analysis and finite element simulation. A tensile test on the cosine honeycomb is also carried out. Based on this，a flexible trailing edge based on a two-dimensional deformable zero Poisson’s ratio cosine honeycomb was designed，and the bending performance of the cosine honeycomb trailing edge section is simulated and analyzed. The results show that the in-plane elasticity and stress state of the cosine honeycomb structure are superior to other three honeycomb structures. The quasi-linear strain of the cosine honeycomb achieves 27.8%. Excellent bending performance of cosine honeycomb segment can be achieved by parameter adjustment，thereby achieving significant bending deformation of the flexible trailing edge structure. This study can provide references for the design and analysis of novel flexible trailing edge structures.